Determinants of inclusive economic growth in Indonesia moderated by the open unemployment rate - Alam, Wira Yudha; Fitrianto, Hari (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study intends to find empirical evidence regarding the influence of the democracy index, government expenditure on education, and income inequality on inclusive economic growth moderated by the open unemployment rate. Method – This research employs a quantitative methodology with panel data regression. Utilizing secondary data from Indonesia's report on inclusive economic growth. The data was generated in numerical form from 33 provinces in Indonesia from 2019 to 2023. In this study, the number of observation data or samples used is 165. The data analysis used is the panel data regressions and moderated regression analysis (MRA) method with EViews 12. The selected model is the fixed effect model because of the Chow and Hausman tests. Findings – The research findings indicate that the democracy index and open unemployment rate negatively affect inclusive economic growth. Meanwhile, government expenditure on education positively affects inclusive economic growth. In contrast, income inequality does not affect inclusive economic growth. The open unemployment rate can strengthen the effect of government expenditure on education on inclusive economic growth. However, the open unemployment rate does not moderate the relationship between the democracy index and income inequality on inclusive economic growth. Implications – The study findings contribute to the scientific understanding of inclusive economic growth determinants in Indonesia, a moderate and low-income nation. This research can be a reference for the government in making policies and increasing justice in various fields, such as politics, social issues, and education.